Genome-Wide Association Study and Gene-Based Analysis of Participants With Hemophilia A and Inhibitors in the My Life, Our Future Research Repository - Lessard, Samuel; He, Chunla; Rajpal, Deepak K.; Klinger, Katherine; Loh, Christine; Harris, Tim; Dumont, Jennifer (Frontiers in Medicine, 2022)
Introduction Up to 30% of patients with hemophilia A develop inhibitors to replacement factor VIII (FVIII), rendering the treatment ineffective. The underlying mechanism of inhibitor development remains poorly understood. The My Life, Our Future Research Repository (MLOF RR) has gathered F8 and F9 mutational information, phenotypic data, and biological material from over 11,000 participants with hemophilia A (PwHA) and B enrolled across US hemophilia treatment centers, including over 5000 whole-genome sequences. Identifying genes associated with inhibitors may contribute to our understanding of why certain patients develop those neutralizing antibodies. Aim and Methods Here, we performed a genome-wide association study and gene-based analyses to identify genes associated with inhibitors in PwHA from the MLOF RR. Results We identify a genome-wide significant association within the human leukocyte antigen (HLA) locus in PwHA with F8 intronic inversions. HLA typing revealed independent associations with the HLA alleles major histocompatibility complex, class II, DR beta 1 (HLA DRB1*15:01) and major histocompatibility complex, class II, DQ beta 1 (DQB1*03:03). Variant aggregation tests further identified low-frequency variants within GRID2IP (glutamate receptor, ionotropic, delta 2 [GRID2] interacting protein 1) significantly associated with inhibitors. Conclusions Overall, our study confirms the association of DRB1*15:01 with FVIII inhibitors and identifies a novel association of DQB1*03:03 in PwHA carrying intronic inversions of F8. In addition, our results implicate GRID2IP, encoding GRID2-interacting protein, with the development of inhibitors, and suggests an unrecognized role of this gene in autoimmunity.